If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 5a = 2a + 9 Reorder the terms: -9 + 5a = 9 + 2a Solving -9 + 5a = 9 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -9 + 5a + -2a = 9 + 2a + -2a Combine like terms: 5a + -2a = 3a -9 + 3a = 9 + 2a + -2a Combine like terms: 2a + -2a = 0 -9 + 3a = 9 + 0 -9 + 3a = 9 Add '9' to each side of the equation. -9 + 9 + 3a = 9 + 9 Combine like terms: -9 + 9 = 0 0 + 3a = 9 + 9 3a = 9 + 9 Combine like terms: 9 + 9 = 18 3a = 18 Divide each side by '3'. a = 6 Simplifying a = 6
| -2n+7=4 | | -25p=200 | | 4x-6(3x+4)= | | 7(6-9)=-21 | | 28-6n+7(2n-8)-3n=0 | | -126=-18c | | 4b^2+20b+25=0 | | 2(7-x)+4c=20 | | 2(x-5)4=-4(-7x+6)-8x | | 3(4g+1)-g=1-(-11g-2) | | -17+3x=13 | | .13x-1.4=.08x+7.6 | | 6x+11=9x+14 | | 2/-5=-30 | | -4b-5=36+9 | | N/-5=30 | | y-(19)=25 | | 10x+2=-5(x-6) | | 8x-7=5x-10 | | 2+n*3=n*4 | | Xsquared+96+17x=180 | | 5(3x+1)-2(x+6)= | | 4(u+1)=-2(8u-3)+2u | | -30+14x=4x | | 4y^2+9=6y | | (7/8)-((1/3)n)=(1/4)n-3/4 | | -7+2n=7(7n-1) | | 2(x-5)+2x=4(x+2)-18 | | -(n+4)=21 | | -5.6(q-3.2)-4.5q+3.6-q= | | 3491.88=1680+150.99x | | 4(2-6x)-6=8x[-(3x-11)+20] |